Cosine response of an Indian pyranometer - DESlKAN, V.; KANADE, V.V. (MAUSAM, 1997)
ABSTRACT .The performance of a pyranometer depends on various characteristics like spectral response, linearity of output. temperature coefficient and dir tional response" The departure from the cosine law is one of the most difficult to correct for and even to determine individually" The Central Radiation Laboratory has carried out the determination of cosine error at Pune. The results of such a measurement on an Indian made thermoelectric pyranometer are IX"esented and discussed"